Estudo histórico sobre a recepção da análise do comportamento de B. F. Skinner pelo campo educacional no Brasil (1961 – 1996) - Sérgio Domingues (2019)
The main goal of this research is to present a historical study in which it was investigated the process of response from Behavioral Analysis, science founded by B. F. Skinner, in Brazil’s educational field. The theoretical framework used in the making of this research was based upon the concept of psychology theories response. The concept of response, includes the acceptance and theoretical appropriation, followed by a exchange the original theory and it’s new accepted and appropriated version in a new context. This approach allows theoretical benefits to investigate the way psychological theories can be received in sociocultural environments that differ from the ones they were originally elaborated on. On this research, when evaluating the response to the Behavioral Analysis in Brasil’s educational field process. The message (concepts and principles of Behavioral analysis), the emitters (writers who founded and disseminated the theory, such as B.F. Skinner and Fred Keller) and the ones who received it (professors) were analyzed. The process of response takes in consideration, still, the problematic and intellectual interests present in the disciplinary field in which the theory is inserted. In this case the problematic and the intellectual interests in the Brazilian educational field in the period between the National Education Guidelines and Bases Act of 1961 and 1996 are analyzed, what explains and it’s showed as the time frame for this research. The applied methodology consisted of the analysis of four sources: the editions of the Brazilian Journal of Pedagogical Studies - RBEP, published between 1961 and 1996, in which were sought to identify texts (articles, reviews, lists of bibliographies) that made reference to Skinner and teaching technology; The second source of research was the syllabus of Psychology subjects of the Pedagogy course of the Federal University of Viçosa - UFV, in these syllabus were identified concepts and principles of Behavior Analysis, that were grouped at five-year intervals. From this we proceeded a quantitative analysis of the number of concepts and principles present in each period in teacher training; the third source was the teaching plans of the subjects of Psychology and Education of the Pedagogy course offered at the Faculty of Education of the Federal University of Minas Gerais, from which was sought to identify in which disciplines Behavior Analysis was taught and which works were used in the teaching of its concepts and principles. The fourth source consulted was professors who were involved in receiving the Behavior Analysis in the educational field. Four professors were interviewed according to the oral history methodology. The interviews, after transcribed, were transformed into texts. The content analysis procedures guided the analysis of the teaching plans, as well as the interviews. The results indicate that the Behavioral Analysis was received by the educational field in Brazil in different ways between 1961 and 1996. From the 1960s until the early 1970s, the reception of Behavior Analysis was marked by the personal characteristics of the teachers who had first contact with it, highlighting the role of teachers interested in a scientific psychology and who were involved with left-wing political movements, in favor of a liberating pedagogical conception. From the 1970s, after the 1968 University Reform and the High School Reform in 1971, there was a change in the problematics of national education, which became more technical teacher education and educational management linked to the theory of the human capital. During this period, between the early 1970s and the first half of the 1980s, intellectual interests turned to so-called teaching technologies. These changes in the educational field led to an appropriation of Behavioral Analysis, increasing the interest in technology derived from its concepts and principles. The interest in Programmed Instruction and teaching technology is growing at this moment, giving rise to what some authors define as a technicist pedagogical conception. From the second half of the 1980s onwards, political changes occurred in the country, along with the emergence of more sociological bias theories, such as critical theories in Education, represented in Psychology by the School of Critical Psychology, led to a vehement critique of Behavior Analysis, as a theory that served as the basis for pedagogical technicism, leading to the near disappearance of Behavior Analysis from the educational debate. During this period, in the early 1990s, the Brazilian Association of Psychotherapy and Behavioral Medicine (ABPMC) was founded, and the development of behavioral science began to be discussed within its own field, leading to an increasing isolation of the theory, generating a gap between the two disciplinary fields: Behavior Analysis and Education. It is concluded that the Behavior Analysis was not always received by the educational field in Brazil as part of a technical pedagogical perspective, having initially been received as a theory compatible with liberating pedagogical conceptions, committed to the analysis of the social determinants that shape the behaviors of people. Only posteriorly, from changes in the educational field, did a technicist form of appropriation of Behavior Analysis occur, often from misinterpretations of the theory. These misconceptions became the target of criticism of the so-called critical theories in education, leading to the removal of Behavioral Analysis from the educational debate, causing its isolation as a disciplinary field from the 1990s.